2021
DOI: 10.3855/jidc.14730
|View full text |Cite
|
Sign up to set email alerts
|

Central line-associated bloodstream infection trend in Brazilian adult intensive care units: an ecological study

Abstract: Introduction: Central line-associated bloodstream infections are the second most frequent infection in intensive care units. It represents an adverse event of significant magnitude, thus threatening the patient safety. The aim of this study was to analyze the historical trend of central line-associated bloodstream infections in patients in intensive care units, the rate of infection, central venous catheter utilization ratio, type of pathogen and their antimicrobial resistance pattern. Methodology: This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
(24 reference statements)
0
3
0
1
Order By: Relevance
“…Policimbac® is one of the main manufactured polymyxin B plate used in Brazil and their inaccuracy represent a significant problem, as polymyxin B is still an important therapeutic choice for multidrug-resistant Gram-negative isolates, including K. pneumoniae . KPC-producing K. pneumoniae is the first Gram-negative pathogen associated to bloodstream infection in patients in intensive therapy units from Brazil ( Gomes et al., 2021 ). K. pneumoniae clinical isolates commonly do not present borderline MICs for polymyxins, in this way, a high categorical agreement and absence of very major errors was observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Policimbac® is one of the main manufactured polymyxin B plate used in Brazil and their inaccuracy represent a significant problem, as polymyxin B is still an important therapeutic choice for multidrug-resistant Gram-negative isolates, including K. pneumoniae . KPC-producing K. pneumoniae is the first Gram-negative pathogen associated to bloodstream infection in patients in intensive therapy units from Brazil ( Gomes et al., 2021 ). K. pneumoniae clinical isolates commonly do not present borderline MICs for polymyxins, in this way, a high categorical agreement and absence of very major errors was observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…We identified 11 recent studies that provided insight into the occurrence, microbiology, and determinants of primary BSI in the critically ill [7 ▪▪ ,8 ▪ ,9–13,14 ▪ ,15,16] (Table 1).…”
Section: Epidemiologymentioning
confidence: 99%
“…Gomes Resende da Silva et al investigated CA-BSI incidence in 42 Brazilian ICUs and found a rate of 2.3 to 3.2 per 1000 catheter days with the most frequent organisms being coagulase-negative staphylococci, Klebsiella pneumoniae , Acinetobacter spp. and Pseudomonas aeruginosa [11]. Badia-Cebada et al reported on surveillance of hospital-acquired, CA-BSI in 55 hospitals in Catalonia, Spain during 2007–2019 [12].…”
Section: Epidemiologymentioning
confidence: 99%
“…Para Silva et al (2021) a IPCS tende a se manter incidente dentro das UTI, Staphylococcus coagulase-negativo, K.…”
Section: Base Deunclassified